2021
DOI: 10.1088/1742-6596/1988/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid (DNA) Splicing System from Graph Theoretic Perspective

Abstract: In 1987, Head introduced the recombinant process of deoxyribonucleic acid (DNA) splicing system through a framework of Formal Language Theory. To express this phenomenon, a comprehensive writing system of the rule sets, proper terms and definitions pioneerly introduced by Head. The analysis on the recombinant behavior of double-stranded DNA molecules, characteristics and various type of splicing systems has sparks the researcher to explore more splicing mechanism extensively. The aim of this paper is to give a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Other than that, it also linked to cluster 5 that discussed on the mathematical approach in solving problems in splicing system. This is supported by comprehensive review conducted by Mohd Ruslim et al, [44] that gave an insightful overview on the adoption of graphical approach in DNA splicing system.…”
Section: Co-authorship (Cited Authors)mentioning
confidence: 66%
“…Other than that, it also linked to cluster 5 that discussed on the mathematical approach in solving problems in splicing system. This is supported by comprehensive review conducted by Mohd Ruslim et al, [44] that gave an insightful overview on the adoption of graphical approach in DNA splicing system.…”
Section: Co-authorship (Cited Authors)mentioning
confidence: 66%
“…Previously, multiple researches were conducted by adopting various types of graphs either to present the splicing system or the splicing language. This can be seen from an exhaustive review of DNA splicing system from graph perspective conducted by Mohd Ruslim et al, [13], for instance, limit graph [14,15], de Bruijn graph [16] and cycle graph [17]. In this paper, the formation of splicing languages from the wet model is represented in directed splicing graph.…”
Section: Crick Complementarity Adenine (A) Bonds To Thymine (T) While...mentioning
confidence: 97%
“…These studies also adopted mathematical approaches in presenting their results; via limit adjacency matrix [8], de Bruijn graph [9], and automata diagram [10]. A comprehensive review [11] on the DNA splicing system from graph theoretic perspective showed that DNA is best presented in graphs, as shown in [12][13][14].…”
Section: Introductionmentioning
confidence: 99%